(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Laparoscopic appendicectomy (LA) is a procedure widely performed for acute appendicitis. Evidence suggests lower wound infection and faster recovery than open appendicectomy (OA). But concerns persist about intra-abdominal abscesses (IAA) and other complications. Objective: To estimate pooled incidence and comparative risks of key complications following LA and to examine effects of disease severity (complicated vs uncomplicated) and age (paediatric vs adult). Methods: Systematic search (PubMed, Embase, Cochrane CENTRAL) for RCTs and observational cohorts (≥20 patients) from 1990–2025 reporting complications after LA. Dual screening and extraction: Risk of bias (RoB) 2 for RCTs and Newcastle–Ottawa Scale for cohorts. Random‑effects meta‑analyses: Transformed pooled proportions for incidence, pooled RRs for comparative studies; Heterogeneity via I2 and Q; subgroup and sensitivity analyses. Results: 142 studies included (34 RCTs, 108 cohorts with total LA patients ≈212,000). Pooled overall complication rate 6.2%; SSI 2.8% (RR LA vs OA ≈0.46); IAA 1.9% (RR LA vs OA ≈1.18, not consistently significant). Reoperation 1.1%; mortality 0.08%. Complicated appendicitis is associated with higher complications. Conclusions: LA reduces SSI and LOS compared with OA. Overall complication rates are low. Increased IAA risk is principally a concern in complicated appendicitis. Therefore, careful technique and surveillance recommended.